THE IMPACT OF SOCIAL MEDIA ON THE MENTAL HEALTH OF YOUNG PEOPLE - Berdiqulova Mahbuba Erkinjon qizi,; Nurboyeva Pokiza Erkinjon qizi, (TADQIQOTLAR, 2026)
In the modern digital era, social media has become an essential part of everyday life, especially for young people. Platforms such as Instagram, TikTok, and Facebook allow  individuals  to  communicate,  share  information,  and  express  their  thoughts. Although  social  media  provides  many  opportunities  for  connection  and  learning, researchers  are  increasingly  concerned  about  its  psychological  effects.  This  article explores the impact of social media on the mental health of young people, discussing both positive and negative consequences, as well as strategies for maintaining a healthy digital lifestyle.